Strategi Pengembangan Usahatani Jeruk Siam di Desa Sekardadi Kecamatan Kintamani Kabupaten Bangli (Jurnal Agribisnis dan Agrowisata, 2025)
Development Strategy of Siam Citrus Farming in Sekardadi Village, Kintamani District, Bangli Regency. Siam citrus is the main commodity that is cultivated in Sekardadi Village. Siam citrus farming has an important role in the economic development of the community in Sekardadi Village, especially farmers. The development of Siam citrus farming in Sekardadi Village is still not optimal due to several factors, one of which is the increase in production costs. This study aims to determine internal and external factors and formulate alternative strategies for the development of Siam citrus farming in Sekardadi Village, Kintamani District, Bangli Regency. Identification of the internal factors of Siam citrus farming in Sekardadi Village in the form of strengths and weaknesses, and external factors in the form of opportunities and threats. Based on the EFAS and IFAS matrices, in the SWOT analysis diagram, Siam citrus farming in Sekardadi Village is in quadrant I, which means that Siam citrus farming has great strength so that it can take advantage of existing opportunities. These conditions support an aggressive growth policy. The results of the SWOT Matrix obtained alternative strategies, namely the S-O strategy by increasing production yields in terms of quality and quantity by optimizing the use of available land and production facilities to meet market demand, developing agrotourism based on Siamese oranges, and utilizing information technology; W-O strategy by increasing farmers' knowledge regarding the wise use of chemical pesticides and land management by utilizing information technology and implementing an integrated farming system; S-T strategy by increasing the productivity of Siamese citrus plants using available facilities and infrastructure wisely to anticipate pest and disease attacks; and the W-T Strategy by increasing cooperation with government agencies in procuring fertilizer subsidies and training or counseling related to the use of pesticides and chemical fertilizers, pest and disease control, as well as soil management and reducing the use of synthetic pesticides.